2014
DOI: 10.1371/journal.pone.0091789
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Experimental Evolution of the Bacillus cereus-Ketogulonicigenium vulgare Co-Culture

Abstract: The microbial co-culture system composing of Ketogulonicigenium vulgare and Bacillus cereus was widely adopted in industry for the production of 2-keto-gulonic acid (2-KGA), the precursor of vitamin C. We found serial subcultivation of the co-culture could enhance the yield of 2-KGA by 16% in comparison to that of the ancestral co-culture. To elucidate the evolutionary dynamics and interaction mechanisms of the two microbes, we performed iTRAQ-based quantitative proteomic analyses of the pure cultures of K. vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Our previous studies13 identified that K150 acquired more capability compared with K0 in protein degradation. Amidohydrolase (or amidase) is a type of hydrolase that acts upon amide bonds.…”
Section: Resultsmentioning
confidence: 98%
“…Our previous studies13 identified that K150 acquired more capability compared with K0 in protein degradation. Amidohydrolase (or amidase) is a type of hydrolase that acts upon amide bonds.…”
Section: Resultsmentioning
confidence: 98%
“…A metabolomics analysis has detected a number of metabolites exchange among K . vulgare and the Bacillus strain [ 8 ], where the transport system of the membranes plays an important role [ 65 ]. B .…”
Section: Resultsmentioning
confidence: 99%
“…In response to starvation for sources of carbon, nitrogen, or phosphorus, sporulation can be initiated in B. megaterium [25]. Sporulation of B150 was less than B0 [26] in the co-culture, which might be due to enhanced capability of nutrition intake in B150. Thus, the swarming motility of B150 in the co-culture reduced comparing with B0.…”
Section: Discussionmentioning
confidence: 96%